Selected Topics on Business Informatics: Editorial Introduction to Issue 31 of CSIMQ - Bartosz Marcinkowski (Complex Systems Informatics and Modeling Quarterly)
This thematic issue introduces two structured literature review articles as well as a couple of empirical ones. The authors of the literature reviews move into the broad field of assuring the quality of IT artifacts, focusing on different dimensions of the software engineering process. With the ever-increasing scale of computerization in more and more areas of life, insufficient emphasis on quality is not only associated with significant costs of bug-fixing. After all, considerable risks arise from the possibility of exploiting the vulnerabilities of the target product. In extreme cases, poor quality can lead to loss of health and life. Not surprisingly, academics and practitioners alike have been looking at this challenge for many years, and from numerous perspectives. The quality of IT artefacts also depends on the education of professionals and good understanding of application domains. The empirical papers concern educational issues regarding Enterprise Architecture and deepen our understanding of decentralized autonomous systems.